New PK/PD profile improvement following cephalosporin extended infusion : a systematic review - Nurani, Melisa Rizky; Widyati, Widyati Widyati; Yasin, Nanang Munif (Faculty of Pharmacy, Universitas Pancasila, 2024)
Antimicrobial resistance is a global problem that is currently experienced in various countries, both developed and developing countries. The lack of discovery of new antibiotics and the increasing incidence of Multidrug–Resistant Organisms (MDROs) have sparked several efforts to optimize the administration of currently available antibiotics. Modifications in the pharmacokinetic and pharmacodynamic profiles are one of the strategies carried out, namely by extending the duration of infusion. Cephalosporins are time-dependent antibiotics; the longer they are exposed to an infusion, the more potent they are against bacteria. This is so that the drug concentration can remain above the MIC (Minimum Inhibitory Concentration) for an extended period of time throughout the infusion. In this study, articles available in Pubmed and Google Scholar from 2013-2023 using the PRISMA method related to the extension of the duration of cephalosporin infusion were evaluated. The search strategy used the keywords continuous infusion, extended infusion, prolong infusion, cefazolin, cefuroxime, ceftriaxone, ceftazidime, cefotaxime, and effectiveness. From the research results, it was found that continuous infusion was better able to achieve the desired target drug levels compared to intermittent infusion and IV bolus administration.